Emotional Intelligence and Academic Anxieties: A Literature Review. Issue 1 (2nd January 2017) - Jan, Sajjad Ullah; Anwar, Mumtaz Ali; Warraich, Nosheen Fatima
ABSTRACT: Emotional intelligence is an important area of psychology, which has gained acceptance in almost every academic discipline. It also seems to influence the various academic activities undertaken by students. This article, which is part of a larger study, reviews the literature on emotional intelligence, and its relationship with the academic and nonacademic characteristics of students with an emphasis on the significance of this relationship. This review shows that emotional intelligence of students is a key element for them while handling a stressful situation. It also illustrates that emotional intelligence can be supportive in managing library anxiety among students leading to better academic performance. This article will assist the academic librarians to recognize the role of emotional intelligence in library-related activities of the patrons. It is recommended that future research should give more attention to this area.